2021
DOI: 10.3347/kjp.2021.59.2.153
|View full text |Cite
|
Sign up to set email alerts
|

First Clinical Cases of Spirometrosis in Two Cats in Korea

Abstract: This study reports the first two clinical cases of spirometrosis caused by <i>Spirometra</i> sp. in cats in Korea. In these two cases, the cats vomited, and long proglottids of tapeworm were recovered. The sick cats presented with anorexia and lethargy. However, they unexpectedly showed no diarrhea, which is the main symptom of spirometrosis. Based on a fecal floatation test as well as morphological and molecular analyses, the parasite was diagnosed as <i>Spirometra</i> sp. The 2 cases … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…Sparganosis caused by the Spirometra genus in humans and animals is well known in Korea (11,14). In contrast to two cats living in the cities of Yangsan and Daegu in South Korea (14), the cat described in this study showed no clinical signs of parasitic infection, such as diarrhea, vomiting, weight loss, or anemia. No abnormalities were noted in blood morphology or typical serum biochemistry, except for a low folate level.…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Sparganosis caused by the Spirometra genus in humans and animals is well known in Korea (11,14). In contrast to two cats living in the cities of Yangsan and Daegu in South Korea (14), the cat described in this study showed no clinical signs of parasitic infection, such as diarrhea, vomiting, weight loss, or anemia. No abnormalities were noted in blood morphology or typical serum biochemistry, except for a low folate level.…”
Section: Discussionmentioning
confidence: 53%
“…The cat imported into Poland without any preventive measures (vaccination and deworming) or prior veterinary examinations was adopted at the beginning of 2023 as a stray cat. Stray cats play a significant role as definitive hosts for many tapeworm species belonging to the genera Taenia, Mesocestoides, Echinococcus, Dibothriocephalus, and Spirometra (3,13,14,23,27,28). Dogs and cats are recognized as the most important animal hosts in endemic and urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…This result suggests that S. mansoni commonly infect companion animals and mammalian wildlife, although the number examined is too small for the data to be concluded. It is known that S. mansoni is widely distributed in Asia [ 8 , 22 , 23 ] and S. mansoni infections in cats and dogs have also been reported in China [ 2 ] and South Korea [ 6 ]. The etiological agents in Chinese and Korean reports were identified due to morphology and molecular diagnosis, respectively.…”
mentioning
confidence: 99%